Non-descent vaginal hysterectomy in previous cesarean section: a retrospective study - Jacob, K. J.; B., Divya M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Non-descent vaginal hysterectomy (NDVH) is removal of uterus through vagina in non-prolapsed uterus. As there is an increase in caesarean section, hysterectomy in women with previous caesarean section is also increasing. The objective of this study is to assess the feasibility and safety of non-descent vaginal hysterectomy in patients with previous caesarean section. Methods: This is a retrospective study conducted in the department of obstetrics and gynecology, Government Medical College, Thrissur from January 2017 to December 2018. Non-descent vaginal hysterectomy in 24women with previous caesarean section was studied. Details regarding age, parity, number of caesarean sections, indication of surgery, intraoperative and postoperative complications were evaluated. Results: All 24 women underwent non-descent vaginal hysterectomy successfully. 10 women (41.7%) were between 46-49 years. Commonest indication of hysterectomy was fibroid uterus (41.7%) and most common complaint was heavy menstrual bleeding (79%). There was bladder injury in one woman with history of previous 2 caesarean section. 3 women developed UTI in postoperative period. Conclusions: Vaginal hysterectomy is associated with lower complications and more rapid recovery. A successful NDVH in previous caesarean section depends on the expertise and experience of the surgeon. NDVH in previous caesarean is safe in expert hands.